Menilai Kinerja Penyelenggara Pemilu - Gandha Widyo Prabowo (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2023)
This article found that the performance of the KPU as an election organ in Indonesia is greatly influenced by the complexity of internal and external situations. The KPU is faced with demands to work optimally according to the parameters of the law in implementing decisions to hold general elections. What the KPU does must comply with constitutional standards and election regulations, or not tolerate even the slightest malpractice in the administration. Through the participant method, it was found that the internal aspects of the KPU are very dependent on the capacity of human resources with regard to electoral techniques. While the external aspect is a form of supervision from the outside that functions as a supervisory institution for upholding the principles of accountability, transparency, and integrity in order to prevent potential malpractice in the administration of elections.